2012
DOI: 10.1071/fp11269
|View full text |Cite
|
Sign up to set email alerts
|

Partial rootzone drying increases water-use efficiency of lemon Fino 49 trees independently of root-to-shoot ABA signalling

Abstract: To determine whether irrigation strategy altered the sensitivity of Citrus leaf gas exchange to soil, plant and atmospheric variables, mature (16-year-old) Fino 49 lemon trees (Citrus limon (L.) Burm. fil. grafted on Citrus macrophylla Wester) were exposed to three irrigation treatments: control (irrigated with 100% of crop potential evapotranspiration, ET c ), deficit irrigation (DI) and partial rootzone drying (PRD) treatments,which received 75% ET c during the period of highest evaporative demand and 50% ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 45 publications
5
22
0
1
Order By: Relevance
“…In general, under soil drying, roots produce more ABA than normal conditions (Davies and Zhang 1991). Increased ABA transmits chemical signals (CSs) to shoot via xylem transpiration stream and decreases stomatal conductance (Liu et al 2006, Perez-Perez et al 2012, Amjad et al 2014. Similar is the case in the current experiment where leaf ABA concentration increased linearly under DI and ARD.…”
Section: Discussionsupporting
confidence: 75%
“…In general, under soil drying, roots produce more ABA than normal conditions (Davies and Zhang 1991). Increased ABA transmits chemical signals (CSs) to shoot via xylem transpiration stream and decreases stomatal conductance (Liu et al 2006, Perez-Perez et al 2012, Amjad et al 2014. Similar is the case in the current experiment where leaf ABA concentration increased linearly under DI and ARD.…”
Section: Discussionsupporting
confidence: 75%
“…A/Gs and A/E are very important for plant development under water limited conditions, such as in semi-arid regions. Studies have identified citrus plants with high A/Gs, such as those exhibited by SM, as suitable for semi-arid regions and/or regions with partial irrigation methods8293031.…”
Section: Discussionmentioning
confidence: 99%
“…The stomatal closure observed in quinoa plants of present study could be attributed to increased ABA contents under water‐limited conditions. At higher concentration, ABA acts as signalling molecule to induce stomatal closure which eventually decrease conductance (Amjad et al., ; Pérez‐Pérez, Dodd, & Botía, ). This also evidenced from significant negative correlation between ABA and stomatal conductance (Figure a).…”
Section: Discussionmentioning
confidence: 99%